Case Report: Percutaneous Cholecystostomy as the Beginning of Recovery - Gudelytė, Gabrielė; Sileikis, Audrius (Lietuvos chirurgija, 2024)
Background. Acute cholecystitis is one of the most frequent urgent diseases in elderly patients. Usually, the management of acute cholecystitis is through laparoscopic surgery, however, for critically ill patients it might be a dangerous invasive procedure. Therefore, percutaneous cholecystostomy is used. Hence, wordwise the role of percutaneous cholecystostomy for acute cholecystitis is controversial. Case presentation. We report the case of a 78-year-old man who was diagnosed with acute calculous cholecystitis. The patient was admitted in poor condition and over 3 days it became worse. Due to the patient’s high comorbidity index a percutaneous cholecystostomy was performed. In the postoperative course, it is complicated with subcapsular hematoma and tube dislocation. Four months later, laparoscopic cholecystectomy was performed. The postoperative period was uneventful and outcomes were excellent.Conclusion. In conclusion, percutaneous cholecystostomy can be successful and a valuable option in the short-term treatment of critically ill patients. Although, we believe that these patient’s management decision is based on the surgeon’s clinical judgment and should be individual.